2022
DOI: 10.1016/j.jaip.2021.10.050
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Symptoms Are Attenuated in Moderate-to-Severe Atopic Dermatitis Patients Treated with Dupilumab

Abstract: What is already known about this topic? Preliminary data suggest increased type 2 cytokines during the COVID-19 cytokine storm. However, it remains unclear how COVID-19 outcomes differ between patients with atopic dermatitis (AD) on type 2etargeting agents (dupilumab) and those treated with other systemics or topical treatments.What does this article add to our knowledge? This is the first study to directly compare the severity of COVID-19 symptoms in patients with moderate-to-severe AD on different treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 34 publications
2
51
1
Order By: Relevance
“…Through utilization of two databases, we have found that prior dupilumab usage in COVID-19 patients was associated with improved survival compared to matched controls. Previous work by Ungar et al, 2022 supported this finding, where, in atopic dermatitis patients dupilumab use was also associated with a reduction in severe outcomes from COVID-19 (Ungar et al 2022). We report these findings building off of in vivo work supporting a causal role for IL-13 in COVID-19 pathogenesis.…”
Section: Discussionmentioning
confidence: 64%
“…Through utilization of two databases, we have found that prior dupilumab usage in COVID-19 patients was associated with improved survival compared to matched controls. Previous work by Ungar et al, 2022 supported this finding, where, in atopic dermatitis patients dupilumab use was also associated with a reduction in severe outcomes from COVID-19 (Ungar et al 2022). We report these findings building off of in vivo work supporting a causal role for IL-13 in COVID-19 pathogenesis.…”
Section: Discussionmentioning
confidence: 64%
“… 8 Furthermore, the elevation of Th2 cytokines in serum of COVID‐19 patients was reported repeatedly specially during the cytokine storm. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Hence the latter two interleukins have crucial role in the pathogenesis of AD 10 ; in this context dupilumab was the first FDA approved immunomodulatory medication to treat moderate to severe AD. 1 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Dupilumab has since been shown to reduce symptom severity and improve clinical outcomes in other observational studies utilizing large patient databases 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients on dupilumab had a 12.3% absolute risk reduction in mortality compared to a propensity score matched sub cohort of 81 patients with COVID-19 not on dupilumab but with atopic diseases for which dupilumab is routinely used 9 . Dupilumab has since been shown to reduce symptom severity and improve clinical outcomes in other observational studies utilizing large patient databases 17,18 .…”
Section: Introductionmentioning
confidence: 99%